The Selection of Temporary Shelter Areas with Fuzzy TOPSIS Method for the Ankara Province - Mine Ömürgönülşen; Cem Menten (Doğal Afetler ve Çevre Dergisi)
Many people face various types of disasters every year. Within the framework of disaster logistics, temporary shelter areas should be identified before any disaster occurs. The main purpose of this study is to determine the temporary shelter areas in case of a disaster. Fuzzy TOPSIS method was used to fulfill this aim in Ankara due to its being capital and second biggest city of Turkey. In this context, five alternatives were evaluated according to ten criteria determined in accordance with national and international standards by taking expert opinions. Among the five different alternative locations, Etimesgut has been identified as the most suitable temporary shelter area for Ankara. Mamak takes the last place in the ranking. In addition, as a result of the order of alternatives, Yenimahalle was in the second, Çankaya was in the third and Keçiören was in the fourth place in the ranking. Different from the previous studies in the literature, this study focuses on all of the potential disasters. No study has been known on location selection problem of temporary shelter areas after the disaster for Ankara Province.